Ｒesearch on Design Synthesis Methodology in Supporting of Bio-inspired Design Solution Generation - CHEN Ji-yi; MA Jin; HU Jie; QI Jin; PENG Ying-hong (Journal of Harbin University of Science and Technology)
In order to solve the problem of innovative solutions generation in the process of bio-inspired design design solutions generation. Firstly，based on the formerly proposed Function-Behavior-Structure ( FBS) knowledge cells model constructed by the decomposition of case functions，the pre-synthesis step acquires preliminary design solutions through connecting FBS knowledge cells end to end by backtracking the functional decomposition process of design requirements. Secondly，the reasoning step verifies the corresponding behavior attributes，parameters and constraints of the generated preliminary solutions to acquire suggested solutions. Thirdly，the evaluation process based on the fuzzy TOPSIS comprehensive evaluation method further evaluates the quality of suggested solutions to acquire committed design solutions. Finally，the design of a visual prosthetic device is taken as an example to verify the proposed bio-inspired design methodology，and solutions to meet the design requirements are generated. The result shows that the proposed methodology can be used effectively with the retrieved knowledge cells set and ensures the innovativeness and feasibility of the solutions.